2017
DOI: 10.11591/ijere.v6i4.10775
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Literacy Based Critical Reading Teaching Material with Active Readerstrategy for Junior High School

Abstract: This article describes the findings of a study aimed at producing a set of cultural literacy-oriented critical reading teaching material. This material is developed as a countermeasure to the increasingly thin sensitivity of society, especially the students toward noble values of religion, custom, and culture. With this material student get a significant critical understanding of the discourse with the content of noble value of Indonesian culture. The understanding is attained by students through active reader… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The results of the study showed that reading comprehension skills were different in terms of reading literacy levels. This gives a meaning that the higher a person's literacy in reading is predicted to improve reading comprehension skills [2] [18]. As a skill, reading requires exercises like any other skill [19] (Yildiz, 2017).…”
Section: B Discussionmentioning
confidence: 99%
“…The results of the study showed that reading comprehension skills were different in terms of reading literacy levels. This gives a meaning that the higher a person's literacy in reading is predicted to improve reading comprehension skills [2] [18]. As a skill, reading requires exercises like any other skill [19] (Yildiz, 2017).…”
Section: B Discussionmentioning
confidence: 99%
“…Critical reading is also defined as active, careful, reflective, and analytic reading activity as cited by Kurland, 2000 in (Munawaroh, 2013). It ensures that readers are active asking questions, looking for facts, and suspending judgment (Damaianti et al, 2017) and (Suzanne, 2016). Interaction between reader and author is involved mutually and reflecting understanding each other.…”
Section: Critical Reading Strategiesmentioning
confidence: 99%
“…Nasrollahi, Krishnasam & Noor (2015) define CR as an interactive process uses a variety levels of thought and critical readers are asking questions about the text they are reading. Damaianti, Damaianti & Mulyati (2017) illustrate that critical readers should be active readers, asking questions, looking for facts and suspending judgment until they assume right .Abd Kadir, Subki, Jamal& Ismail (2014) indicate that CR skills help students analyze, synthesize and evaluate what is read. Yu (2015) states that to read critically, readers should actively recognize and analyze information they read on the text.…”
Section: Introductionmentioning
confidence: 99%